Prognostic Nomogram for Sorafenib Benefit in Hepatitis B Virus-Related Hepatocellular Carcinoma After Partial Hepatectomy - Dong, Wei; Yan, Kai; Yu, Hua; Huo, Lei; Xian, Zhihong; Zhao, Yanqing; Li, Jutang; Zhang, Yuchan; Cao, Zhenying; Fu, Yong; Cong, Wenming; Dong, Hui (Frontiers in Oncology, 2021)
Background Predicting the long-term prognosis of individuals who experienced sorafenib treatment following partial hepatectomy due to hepatitis B virus (HBV) related hepatocellular carcinoma (HCC) is difficult. This work aims to create an effective prognostic nomogram for HBV related HCC patients who receiving sorafenib treatment as adjuvant therapy after surgery. Methods A total of 233 HBV-related HCC patients treated with or without sorafenib following partial hepatectomy at the Eastern Hepatobiliary Surgery Hospital from 2008 to 2013 were matched with propensity score matching analysis. The optimal cut-off point of the overall survival (OS) factor level was determined by x-tile. The selection of indicators was based on clinical findings. The Cox regression model with an interaction term was employed for evaluating the predictive value. Using a multivariate Cox proportional hazards model, a nomogram was subsequently formulated to analyze 111 patients treated with sorafenib. The nomogram’s discriminative ability and predictive accuracy were determined using the concordance index (C-index), calibration, and ROC curve. Results The matched sorafenib cohort of 111 patients and control cohort of 118 patients were analysed. Subgroup analysis revealed that Low GPC3, pERK, pAKT, serum AFP levels, without MVI, under 50 years old, male, TNM stage I/II and BCLC stage 0/A were significantly associated with a better OS in patients subjected to sorafenib treatment compared to those without sorafenib treatment after surgery. Multivariate analysis of the sorafenib cohort revealed GPC3, pERK, pAKT, serum AST and BCLC stage as independent factors for OS, and all were included in the nomogram. The survival probability based on the calibration curve showed that the prediction of the nomogram was in good agreement with the actual observation. The C-index of the nomogram for predicting survival was 0.73(95% CI, 0.67 - 0.78). The area under the ROC curve (AUC) for the nomogram to predict the survival for 1, 3, and 5-year was 0.726, 0.816, and 0.823, respectively. Conclusion This proposed nomogram shows the potential to make a precise prediction regarding the prognosis of HBV-related HCC patients, and may help to stratify patients for personalized therapy following partial hepatectomy.